"I wld like u WMP to extend electricity 2 our village": On Information Technology and Interest Articulation. Issue 3 (22nd August 2014) - GROSSMAN, GUY; HUMPHREYS, MACARTAN; SACRAMONE-LUTZ, GABRIELLA
<x content-type="archive" xml:space="preserve">Abstract</x> How does access to information communication technology (ICT) affect who gets heard and what gets communicated to politicians? On the one hand, ICT can lower communication costs for poorer constituents; on the other, technological channels may be used disproportionately more by the already well connected. To assess the flattening effects of ICTs, we presented a representative sample of constituents in Uganda with an opportunity to send a text message to their representatives at one of three randomly assigned prices. Critically, and contrary to concerns that technological innovations benefit the privileged, we find evidence that ICT can lead to significant flattening: a greater share of marginalized populations use this channel compared to existing political communication channels. Price plays a more complex role. Subsidizing the full cost of messaging increases uptake by over 40%. Surprisingly however, subsidy-induced increases in uptake do not yield further flattening since free channels are not used at higher rates by more marginalized constituents.